Inclined bite plane for correction anterior crossbite in early permanent dentition - Abdul Malik; Arya Brahmanta (Makassar Dental Journal PDGI Makassar, 2018)
Inclined bite plane is a simple functional appliance used in the lower arch jaw which is work as bite jumper. Anterior crossbite is an indicator of skeletal growth problem and developing class III malocclusion. The aim of this case report is to know the mechanism of inclined bite plane as functional appliance for managing class III malocclusion. In this article we would like to present a 11- year-old boy with class III malocclusion, SNA 76 o , SNB 81 o , ANB –5 o , overjet -3 mm, overbite 5 mm and concave facial profile. The use of acrylic resin in lower arch as an inclined bite plane for anterior crossbite correction in early permanent dentition at adolescent is an effective therapy choice.